Il Gran Sottisier. Mirabilia, falsi e plagi nel giornalismo letterario di Giovanni Pellegrino Dandi - Narros, Jacopo (Consonanze, 2023)
An abbot, a journalist, and a man of letters, Giovanni Pellegrino Dandi (1664-c. 1726) curated, during his frenetic activity, the columns of various literary periodicals. His writings immediately caught the attention of some of the leading Italian intellectuals of his time, from Lodovico Antonio Muratori to Antonio Vallisneri. While filling a gap in the coeval cultural press, Dandi's publications, such as «Gran Giornale de' Letterati» (1701-1704), were, in fact, a fraud. Rather than creating original works, Dandi appropriated writings that had been printed before, and were later forgotten by the readers. Jacopo Narros brings to light the documentation about Dandi's cheatings, creating an entertaining narrative of the editorial nonchalance of this singular erudite, and outlining his fascinating figure of forger and plagiarist. Moreover, by investigating the relationship between the «gran sottisier» and the 17th and 18th century literary community, Narros shows the dynamism of the intellectual life of that period. In those years, erudites like Apostolo Zeno and Scipione Maffei were active in structuring new communicative strategies to transmit innovative scientific discoveries and literary experiences to their readership.